Quantification of the Salivary Steroid Hormones Considered as Bio-markers in Clinical Research Studies and Sports Medicine - Plenis, Alina; Baczek, Tomasz (Current Pharmaceutical Analysis, 2010)
Steroid hormones are important in controlling human body functions as a part of the endocrine system together with neuronal systems and the immune system. Application of the assay of the steroid hormones treated as biomarkers was recently illustrated in certain cases, for example in clinical diagnosis of stress, the Cushing syndrome, congenital adrenal hyperplasia, and infertility, as well as in the field of sports medicine. The assessment of the steroid hormones in the body fluids has so far been typically based on serum and urine. However, the use of saliva as the diagnostic medium has recently grown in popularity among the scientists and clinicians because of sample collection, which is quick, uncomplicated, and non-invasive. Moreover, steroid hormones are not bound to protein in saliva. Therefore, salivary determination is an excellent approach for evaluation of free steroid hormones. The present study provides an overview of the analytical methods applied for salivary steroid measurements in the current clinical laboratory practice. It describes and thoroughly discusses the recent achievements associated with optimisation of the analytical conditions for the steroid assay, obtained through application of the modern separation techniques such as liquid chromatography, mass spectrometry, versus non-separation techniques such as the immunological methods. Moreover, the issues associated with optimization of the extraction procedures are presented, since sample pre-treatment is the most limiting and crucial step in analyses of biological fluids. In addition, the study evaluates the consequences of any pre-analytical variation preceding the application of the assay methodologies, stemming from the collection strategy and the subsequent storage conditions. It further provides several examples of application in diverse fields of interest such as psychology, pharmacology, clinical endocrinology, or sports medicine.
Keywords: Separation and non-separation techniques